Collectors Collect Contemporary : 1990-99. - Institute of Contemporary Art, Boston; Medvedow, Jill S.; Morgan, Jessica (Boston : Institute of Contemporary Art Boston, 1999)
Ali, Laylah ; Artschwager, Richard ; Bartlett, Jennifer ; Bleckner, Ross ; Bourgeois, Louise ; Burton, Richmond ; Butt, Ambreen ; Cinto, Sandra ; Dijkstra, Rineke ; Dill, Lesley ; Friedman, Tom ; Gallagher, Ellen ; Goldin, Nan ; Gonzalez-Torres, Felix ; Gursky, Andreas ; Hamilton, Ann ; Hatoum, Mona ; Herrera, Arturo ; Hodges, Jim ; Kabakov, Ilya ; Kaitz, Sharon ; Kiely, Colleen ; Krisanamis, Udomsak ; LeDray, Charles ; Lemieux, Annette ; Ligon, Glenn ; Long, Charles ; Marshall, Kerry James ; McKie, Todd ; Messager, Annette ; Morell, Abelardo ; Muniz, Vik ; Muñoz, Juan ; Nakamura, Yukiko ; Neto, Ernesto ; Opie, Catherine ; Oursler, Tony ; Pettibon, Raymond ; Pierson, Jack ; Prieto, Monique ; Reed, David ; Richter, Gerhard ; Simpson, Lorna ; Smith, Kiki ; Struth, Thomas ; Taylor-Wood, Sam ; Thurber, Shellburne ; Tomaselli, Fred ; Walker, Kara ; Warrick, Cheryl
biografie
Collectors Collect Contemporary : 1990-99, Institute of Contemporary Art Boston, March 31 - May 28, 1999
Engels
boek